Hydroclimatic and ecohydrological resistance/resilience conditions across tropical biomes of Costa Rica. Issue 6 (7th June 2017) - Esquivel‐Hernández, Germain; Sánchez‐Murillo, Ricardo; Birkel, Christian; Good, Stephen P.; Boll, Jan
Abstract: Water resources management in the tropics is challenged by climate variability and unregulated land use change and their impacts on the complex interactions between vegetation, soil, and atmosphere. This study focuses on the analysis of hydroclimatic and ecohydrological conditions across 6 major biomes in Costa Rica. Using the Budyko and the Tomer–Schilling frameworks, 31 reanalysis data points located across the Caribbean and Pacific domains were classified according to their ecohydrological resistance and resilience between 1989 and 2005. Observed data were used to evaluate the reanalysis products. Resistance was defined as the standard deviation in the water excess (Q/P), whereas resilience was defined as the standard deviation of the energy (AET/PET) to the water excess. A strong orographic separation was obtained between the water‐limited Pacific slope and the energy‐limited Caribbean slope. The Caribbean slope is characterized by low resistance and high resilience to changes in the hydroclimatic conditions, with small relative changes in water excess (−18% to 2.0%), whereas the Northern Pacific slope has high resistance and low resilience and exhibited strong changes in water excess (−34% to 0%). Some regions of the Northern Pacific region covered by lower and premontane forests have recently suffered significant increments in the dryness index (PET/P). This study demonstrates the need for national–regional strategies to effectively optimize water use efficiency and water storage and to include a climate vulnerability component in future water management plans.